Physical education in general education schools in Ukraine (selected aspects) - Władimir Pasicznik (Jan Długosz University in Częstochowa, 2020)
There were many different problems in the organisational process of physical education in schools of Ukraine in the 1990s and at the beginning of the 21st century, such as: underestimation of the importance of physical education in the didactic and educational process by managers of individual schools, insufficient consideration of students' interests in selected forms of exercise; lack of individualisation of work with a student, taking into account their real level of mobility and readiness to perform particular exercises; low level of investment in the development of sports facilities by educational and local authorities, i.e. creating sports fields, swimming pools and supplying schools with sports equipment; lack of coordination in the cooperation of schools with students' parents or with state and local government institutions in the field of popularising physical education and a healthy lifestyle. The Ukrainian children and young people's health situation at the beginning of the 21st century was unsatisfactory. The analysis of pedagogical and specialist literature regarding remedial actions in the pre-school and school education system in physical education in Ukraine shows that most often the main direction of changes is the improvement of methods and forms of conducting physical education lessons as well as activities in the field of popularising sport recreation in the free time and adapting these solutions to contemporary curriculum requirements of this subject at school.